2010
DOI: 10.1590/s1983-41952010000100005
|View full text |Cite
|
Sign up to set email alerts
|

Modelagem computacional de vigas de concreto armado reforçado com fibras de aço submetidas a cisalhamento

Abstract: ResumoComputational modeling has become a common activity to Civil Engineering researchers and professionals. Therefore, the knowledge about the mechanical behavior of materials is very important. To correctly model the mechanical behavior of concrete structures subjected to shear stress, it is necessary to determine the shear retention factor that accounts for the friction between the two surfaces of a crack. The objective of this study is to show how the shear retention factor of steel fiber reinforced concr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The tensile behavior of the steel fiber-reinforced concrete in the V-1-0 beam was represented by a bilinear tension softening diagram, as shown in Figure 9a. The stress and strain values for this diagram were obtained by Araújo et al [5] using an inverse analysis on prismatic specimens under four-point loading, as presented in Table 7. The compressive fracture energy was defined as 100 times the area under the tensile stress-strain curve multiplied by the crack bandwidth, which was adopted as the size of the finite element (10 mm).…”
Section: Materials Properties and Constitutive Lawsmentioning
confidence: 99%
See 2 more Smart Citations
“…The tensile behavior of the steel fiber-reinforced concrete in the V-1-0 beam was represented by a bilinear tension softening diagram, as shown in Figure 9a. The stress and strain values for this diagram were obtained by Araújo et al [5] using an inverse analysis on prismatic specimens under four-point loading, as presented in Table 7. The compressive fracture energy was defined as 100 times the area under the tensile stress-strain curve multiplied by the crack bandwidth, which was adopted as the size of the finite element (10 mm).…”
Section: Materials Properties and Constitutive Lawsmentioning
confidence: 99%
“…There are several methods for modeling cracking in nonlinear finite element analyses of reinforced concrete, with smeared and discrete approaches being the most common. Araújo et al [5] suggested that the discrete crack model is preferable for structures with few cracks. The discrete crack approach considers a crack to be a geometric discontinuity in the finite element mesh; therefore, it is necessary to define the direction and position of cracks before proceeding with the analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation